A study factors contributing towards motor accident in federal highway / Nik Mohd Rabani Wan Ismail - Wan Ismail, Nik Mohd Rabani (Faculty of Business and Management, 2011)
My topic for this project paper is “Factors contributing towards motor accident in federal highway” the rationale of this research is to help the readers to know about the factors causes of increasing number of accidents in federal highway. in my research, i focus more on the factors that contribute to an accident occurred, which is human behavior, motor vehicle condition and weather. for the consequences, it can really help the road user to avoid any unexpected event of accident in the highway and others road as for the guidelines and having the safety journey.